Implementasi Metode Multi Kriteria Dalam Pencarian Produk Apotek - Wiharto, Yudi; Subandi, Subandi; Mufti, Mufti (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2024)
Pharmacy product searches are becoming increasingly important in the context of public health needs. In this digital era, users are often faced with challenges in finding pharmacy products that suit their preferences and needs. In this research, we explore the implementation of multi-criteria methods in pharmacy product searches to increase relevance and search efficiency. Developing a pharmacy product search system that utilizes multi-criteria methods to consider various factors such as description, efficacy, price, availability. Through the integration of this method, the system can present search results that are more personalized and relevant to users. Evaluation of system performance through practical trials and found that the use of multi-criteria methods can improve the quality of pharmacy product search services. This research contributes to the development of more sophisticated and effective pharmacy product search technology, as well as increasing user satisfaction in meeting their health needs